Relaxed Currency Serializability for Middle-Tier Caching and Replication (extended version) - Bernstein, Phil; Fekete, Alan; Guo, Hongfei; Ramakrishnan, Raghu; Tamma, Pradeep (2006)
Many applications, such as e-commerce, routinely use copies of data that are not in sync with the database due to heuristic caching strategies used to enhance performance. We study concurrency control for a transactional model that allows update transactions to read out-of-date copies. Each read operation carries a “freshness constraint” that specifies how fresh a copy must be in order to be read. We offer a definition of correctness for this model and present algorithms to ensure several of the most interesting freshness constraints. We outline a serializability-theoretic correctness proof and present the results of a detailed performance study. This is an extended version of a paper with the same title that appeared in SIGMOD 2006.